Instruments for assessing healthcare professionals’ knowledge, attitudes and practices regarding deprescribing: a scoping review - Ana Carolina Figueiredo Modesto; Luis Phillipe Nagem Lopes; Mariana Del Grossi Moura; Alan Maicon de Oliveira; José Salvador Carrillo; Beatriz Birelli do Nascimento; Flávia Casale Abe; Luciane Cruz Lopes (International Journal of Clinical Pharmacy, 2026)
Abstract Introduction Deprescribing is a multiprofessional process which aims to optimize medication use and improve patient safety, in which healthcare professionals' knowledge, attitudes, and practices (KAP) play a central role. The instruments used to assess KAP among nurses, pharmacists and physicians remain poorly characterised in terms of scope and measurement quality. Aim To map and characterize the instruments used to assess healthcare professionals’ knowledge, attitudes, and practices regarding deprescribing. Method A scoping review was conducted following Joaassess healthcaree (JBI) methodology and reported according to the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Primary studies were eligible if they involved nurses, pharmacists or physicians and applied any instrument assessing KAP related to deprescribing, individually or in combination, regardless of setting or country. Nine electronic databases were searched, including two grey literature sources were searched from inception to September 2024, without restrictions on language or publication date using terms related to nurses, pharmacists, physicians, deprescribing, surveys and questionnaires, and health knowledge, attitudes, and practice Study selection and data charting were performed independently by three pairs of reviewers using a standardised extraction form capturing study characteristics, instrument details, KAP domains assessed, and reported measurement properties. Data was synthesised using descriptive statistics and narrative analysis. The review protocol was registered on the Open Science Framework. Results Of the 3,821 records screened, 49 met the inclusion criteria. Over two-thirds of the included studies were published since 2020 (n = 33, 67.3%). The evidence base was concentrated in high-income countries (n = 36/46, 78.0%; three multi-country studies were not classified by income level), particularly in the Europe and Central Asia region (n = 19, 41.0%), and most often focused solely on physicians, while studies simultaneously involving all three professional groups (physicians, pharmacists, and nurses) were less frequent (n = 8, 16.0%). Instruments commonly assessed multiple KAP domains, especially knowledge, attitudes, and practices combined (n = 12, 30.0%), whereas evidence on psychometric properties was reported in only a minority of studies (n = 13, 26.5%), among these, internal consistency and content validity were the pair most frequently reported together (n = 4, 31.0%). Conclusion Instruments assessing healthcare professionals’ KAP regarding deprescribing remain limited in scope and psychometric robustness. Expanding interprofessional coverage and strengthening validation efforts are key priorities for advancing research in this field.